The convergent threat of ESBL, carbapenemase, and MCR resistance determinants in the Hong Kong food chain: A cross-sectional surveillance study - Wing Ho Li; Tsz Tuen Li; Jordan Yik Hei Fong; Ruheng Chen; Pacy Yin Mei Leung; Elaine Chan; Xueyan Liu; Winnie Wing Yi Tai; Zera Kin Yee Leung; Hwei Huih Lee; Wai-Man Tong; Yan Zhao; et al. (International Journal of Food Microbiology, 2026)

Soil pH drives bacterial community assembly processes and co-occurrence patterns at a regional scale across mountain forests of the Korean Peninsula - Zhi Yu; Lei Chen; Mengchen Zhao; Nan Li; Guanlin Li; Sathiyaraj Srinivasan; Changbae Lee; Dorsaf Kerfahi; Naomichi Yamamoto; Guangyin Zhen; Xueqin Lu; Teng Yang; et al. (CATENA, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Refining the STICS model to predict iceberg lettuce yields based on temperature-dependent photosynthate partitioning - Chu-Chung Chen; Dar-Yuan Lee; Shan-Li Wang; Kai-Wei Juang (Ecological Modelling, 2026)

Mechanistic insights into Cu impurity retention and its effective removal in direct recycling of lithium-ion batteries - Wenlin Yan; Wei Li; Qiushi Miao; Mengchen Liu; Ershuang Lu; Jiao Lin; Minji Lee; Haichen Lin; Shuangjie Tan; Varun Gupta; Zheng Chen; Ping Liu (Chemical Engineering Journal, 2026)

Dragonfly-wing-inspired multifunctional starch-based composite adhesive with enhanced interfacial bonding, durability, and flame retardancy - Yuliang Li; Bowen Liu; Hongda Guo; Seng Hua Lee; Wei Chen Lum; Jianyong Wan; Xiaojian Zhou; Widya Fatriasari; Jun Zhang (Chemical Engineering Journal, 2026)

Bioinspired anisotropic gelatin hydrogels via synergistic crosslinking and structural alignment for ultrahigh mechanical performance and multifunctionality - Wenxing Li; Bowen Liu; Shuduan Deng; Seng Hua Lee; Wei Chen Lum; Xiaojian Zhou; Guanben Du; Widya Fatriasari; Jun Zhang (Chemical Engineering Journal, 2026)

Thiocyanate-driven denitrification with mixotrophic flexibility for real coking wastewater treatment: Novel insights into nitrogen cycling - Yu Zhang; Yu-Tong Li; Quan Zhang; Xue-Ting Wang; Wei Wang; Aijie Wang; Jun Ma; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Water Research, 2026)

Fatty acid composition drives integrated changes in oxidative stability, phytonutrients and processing contaminants of diacylglycerols under thermal stress - Yingyi Zheng; Linjie Chen; Yee-Ying Lee; Mingchen Xu; Chin-Ping Tan; Yong Wang; Aijun Li; Zhen Zhang (Food Research International, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Biodegradable versus persistent nanoplastics reshape nitrogen metabolism and biofilm architecture in denitrifying biofilters - Suhao Feng; Yinzhou Bao; Xiao Zhu; Jiaping Wu; Wenxin Chen; Ding Huang; Tong Zhou; Lijun Meng; Chuang-Hak Lee; Dengxin Li; Manhong Huang (Bioresource Technology, 2026)

PAN4, an AI-designed host-directed immunomodulatory peptide, promotes PGRP-SC1a-associated intestinal immune homeostasis in Drosophila melanogaster - Yanying Sun; Yanan Wei; Wenjie Jia; Xinyue Zhou; Ran Dong; Zekun Wu; Hongyu Miao; ZhenZhi Li; Zheng Chen; Chaoran Liu; Weijie Yuan; Ying Hu; et al. (Insect Biochemistry and Molecular Biology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Recognition of kiwifruit pruning position based on vine segmentation and dormant bud detection with their planar distribution - Shuolin Kong; Bo Jia; Qichen Huang; Juncai Huang; Rui Li; Bao Zhou; Xiancun Zhou; Zhenchao Wu; Jinyong Chen; Xiaoxu Sun; Dateng Zheng; Davut Karayel; et al. (Computers and Electronics in Agriculture, 2026)

Erratum to “Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives” [Water Research, Volume 300, 1 August 2026, 125856] - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Exploring legal‐ and health‐risk messaging to reduce demand for elephant skin - Beilu Duan; Zac Posada‐Baynham; Joceline Yong; Xiaoxi Zhang; Zhan Chen; Anita K. Y. Wan; Jingjing Zhao; Alexander Clark; Lishu Li; Wuji Zheng; Tien Ming Lee (Conservation Biology, 2026)
Asian elephants ( Elephas maximus ) are poached for an illegal trade in their skins, which are used in traditional medicine in Africa and Asia. We explored whether messages about the legal and health risks of using elephant skin for medicinal purposes (stomach illness) could reduce such consumption. We conducted a randomized controlled trial intervention experiment based on a health belief model. We showed 1673 residents at China's Yunnan–Myanmar border comic strips that portrayed these risks (legal‐risk and health‐risk treatments and control). Respondents were then asked for their perception of benefits and risks of using elephant skin and their consumption intentions for treating stomach illness (i.e., seek elephant skin, seek animal‐based traditional medicine, visit informal market, and visit hospitals). We used structural equation models to examine whether and how different messages affect consumption intentions. Compared with the control group ( n = 580), the comics that showed the legal risks of use of elephant skin ( n = 529) significantly reduced respondents’ intentions to seek elephant skin by 24% compared with the control group, particularly when the message conveyed that its use is not a cure. The health‐risk treatment ( n = 564) increased respondents’ intentions to go to the hospital when suffering from stomach illness and, unexpectedly, increased the intention of urban residents who had never heard of elephant skin as a treatment to look for it by 40% compared with those of urban residents in the control group. Our results revealed that interventions tailored to specific audience segments are necessary to prevent unintended, negative consequences of public messaging conservation interventions.

Artificial intelligence for marine oil spill management: Recent advances and future directions - Ziyu Wang; Yawen Huang; Guorui Zhang; Zhihan Wang; Zhi Chen; Catherine N. Mulligan; S. Samuel Li; Maria Elektorowicz; Biao Li; Kenneth Lee; Chunjiang An (Marine Environmental Research, 2026)

Hexamermis jengi n. sp. (Nematoda: Mermithidae) parasitizing grasshoppers and the invasive fall armyworm in Taiwan and Thailand - Ping-Chieh Lee; Ace Kevin S. Amarga; Wen-Hua Chen; Li-Hsin Wu; Chuan-Kai Ho; Chun-I Chiu; Ming-Chung Chiu (Journal of Invertebrate Pathology, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Field experimental investigation of an improved integrated solar collection humidity control and energy recovery ventilation system - Yulu Chen; Akihito Ozaki; Zao Li; Haksung Lee (Building and Environment, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Tackling iron deficiency: the multifunctional benefits of biopolysaccharide-iron(III) complexes from traditional Chinese medicinal plants - Wenyang Zhao; Chun-Wai Mai; Kai Bin Liew; Siew-Keah Lee; Wei Du; Li Chen; Gabriel Akyirem Akowuah; Yik-Ling Chew (Journal of Zhejiang University-SCIENCE B, 2026)

Urinary Fibroblast Growth Factor-23 and Soluble Alpha-Klotho in Cats with Chronic Kidney Disease - Wei-Che Chen; Wei-Li Hsu; Chao-Chin Chang; Pei-Shiue Jason Tsai; Vin-Cent Wu; Ya-Jane Lee (The Veterinary Journal, 2026)

Source-specific VOCs and atmospheric oxidation capacity drive the formation of secondary aerosols and visibility impairment in East Asia suburban environments - Tse-Lun Chen; Kuan-Chieh Lee; Jun-Fa Yeh; Jian-Xian Wu; Li-Hao Young; Neng-Huei Lin; Si-Chee Tsay; Wen-Yinn Lin; Chia-Hsin Lin; Ta-Chih Hsiao (Journal of Hazardous Materials, 2026)

Effects of parachute science on local research capacity 降落伞科学对当地研究能力的影响 - Li Yang; Tao Chen; Colin A. Chapman; Paul A. Garber; Yu Xuan Fan; Tien Ming Lee; Michael Huffman; Juan Carlos Serio Silva; Carlos Peres; Onja H. Razafindratsima; Lwin Ngwe; Peng Fei Fan (Conservation Biology, 2026)
Strengthening research capacity is essential to address the global biodiversity crisis. Yet, parachute science often undermines this goal, and its prevalence, costs, and benefits are unclear. We analyzed 13,502 publications on primate research that we extracted from Scopus (1960–2022) to evaluate the effects of parachute science on local research capacity across primate‐range countries. We categorized these publications as local (LRP), collaborative (CRP), or parachute science (PSRP) research publications and categorized countries where the research took place as low‐ to middle‐income countries or high‐ to upper‐middle‐income countries. We used generalized linear mixed‐effects models to assess how parachute science influenced local research capacity. For 69% of PSRPs, the research was conducted in 59 low‐ to middle‐income countries. For 20% of LRPs, research was led by people from these 59 countries. The disparity in LRPs among country groups was large. Local research publications in high‐ to upper‐middle‐income countries were at least 3.6 times higher than those in low‐ to middle‐income countries. Before 2013, parachute science contributed to an increase in LRPs; this trend reversed after 2013, mainly resulting in a decline in LRPs across all countries and both income categories. Strengthening the capacity to share research in low‐ to middle‐income countries is urgent if international conservation commitments are to be met. We recommend establishing true collaborative and interdisciplinary research teams, expanding local research opportunities, and supporting long‐term research projects as key strategies for sustainable research capacity strengthening in low‐income countries.

Artificial intelligence and automated monitoring for Marine Protected Area Management: A case of Chaojing marine protected area in Taiwan - Yi-Chung Lee; Wen-Hong Liu; Yu-Shiuan Tsai; Li-Shu Chen; Dong-Lin Li (Ocean & Coastal Management, 2026)

High-resolution satellite retrieval of dissolved organic carbon in coastal waters using machine learning: Application to China’s Dongshan Bay - Lingling Li; Xiaolong Yu; Wendian Lai; Nengwang Chen; Weidong Guo; Hongyan Bao; Guizhi Wang; Shuiying Huang; Wenlu Lan; Xiaoyan Peng; Zhongping Lee (Journal of Environmental Sciences, 2026)

Mobile Observations of Intracity Variations in Atmospheric CO2 and CH4 - Jun Wang; Wei Xiao; Ning Hu; Ruonan Li; Honghui Xu; Yibo Liu; Lingbing Bu; Longlong Chen; Yuanze Liu; Xuhui Lee (Advances in Atmospheric Sciences, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

City-scale subsurface utilities mapping by multi-channel ground penetrating radar (MCGPR) with mobile mapping system (MMS) - Wallace Wai-Lok Lai; Phoebe Tin-Wai Wong; Rene Lee-Yee Kwan; Yaxin Li; Yimin Zhou; Wenchao He; Yao Han; Wu Chen (Tunnelling and Underground Space Technology, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Cold Atmospheric Plasma as a Non-Thermal and Biocompatible Disinfection Strategy for Ultrasound Transducers - Ching-Yuan Lin; Kuan-Yi Lee; Dong-Jin Li; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Hobbyist preferences for pet freshwater turtles - Jingjing Zhao; Zhan Chen; Beilu Duan; Wuji Zheng; Anita Kar Yan Wan; Xiaoxi Zhang; Lishu Li; Tien Ming Lee (Conservation Biology, 2026)
The burgeoning pet trade is a primary threat to wild freshwater turtles worldwide. Although the risks from commercial exploitation of turtles have been discussed widely, there is little empirical research on preferences for pet turtles from a hobbyists’ perspective. We conducted an online survey of nearly 2000 turtle hobbyists recruited via discussion forums in China. We collected information on turtle‐keeping experiences, past purchase behaviors, knowledge about the protection status of certain endangered species, and awareness of legality in the trade. We framed discrete choice experiments around different hypothetical scenarios about wild population statuses and captive‐breeding market conditions. We then used a random parameter logit model and a latent class logit model to identify key influencing factors and to explore the level of heterogeneity among turtle hobbyists. Consumers preferred inexpensive turtles, captive‐bred turtles for which traders’ certificates (e.g., business licenses, breeding permits, and proof of legal species origin) were available, online purchase, and delivery by the postal service. They were especially willing to buy turtles for which captive‐breeding techniques were well developed and turtles that had wild populations that were stable or increasing. Preferences were sometimes affected by social factors; for example, some consumers more willingly accepted high‐priced turtles under social influence, rather than when such factors were absent. We identified 3 distinct types of turtle consumers with heterogeneous preferences: 40.3% preferred cheap turtles, 31.1% preferred captive‐bred turtles, and 28.6% preferred both captive‐bred and inexpensive species. Overall, our results can inform interventions and campaigns to conserve freshwater turtles by targeting hobbyists with specific profiles.

Wood oil biodegradation in the marine environment: Behavior, mechanism, and impact - Hongyi Li; Bing Chen; Yiqi Cao; Min Yang; James Brydie; Kenneth Lee; Baiyu Zhang (Water Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Comparison of meiofauna, particularly free-living marine nematode community in interspersed habitats of mangroves and Spartina alterniflora in Zhanjiang, China - H.L. Zhu; K.Y. Gan; N.F.Y. Tam; Z.T. Chen; F.L. Li; S.J.L. Xu; D. Peng; H.C. Zhou; F.W.F. Lee (Marine Pollution Bulletin, 2026)

Differential metabolomic shifts in jellyfish tissues exposed to artificial light spectra - Bonien Chen; Chiu-Hui Kuo; Chen-Hsun Liu; Yung-Kuo Lee; Jui-Kuo Kao; Chih-Hsuan Fan; Feng-Cheng Wu; Li-Lian Liu; Kuohsun Chiu; Yu-Yun Chen (Science of The Total Environment, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Adaptive multi-agent HVAC control for thermal comfort using multi-agent PPO with population-based training - Songze Guan; Ruotian Chen; Jiuwei Liu; Kate Qi Zhou; Xilei Dai; Wentai Li; Sivanand Somasundaram; Alex Chong; Christopher H.T. Lee; Chau Yuen (Energy and Buildings, 2026)

Impact of lactational per- and polyfluoroalkyl substances exposure on infant gut microbiota and potential mediating effects on infant neurodevelopment - Xin Zhang; Huijun Chen; Peng Liu; Yan Zhou; Jiaoyang Li; Hian Kee Lee; Xiaoping Miao; Zhenzhen Huang (Journal of Hazardous Materials, 2026)

Long-term oral administration of inactivated Vibrio harveyi vaccine triggers immunosuppression in Penaeus vannamei - Baozhi Kuang; Wenbin Yang; Changan Li; Choon weng Lee; Bo yu Liu; Chui Wei Bong; Wenqi Wang; Shiyong Chen (Fish & Shellfish Immunology, 2026)

Microphase separation in maltooligosaccharide-based block co-oligomers with dominant sugar volume fractions: Toward a comprehensive understanding of the phase behavior - Chaehun Lee; Taiki Nishimura; Feng Li; Takuya Yamamoto; Redouane Borsali; Kenji Tajima; Hsin-Lung Chen; Toshifumi Satoh; Takuya Isono (Carbohydrate Polymers, 2026)

Experimental and numerical investigation of a roof-integrated solar heating and humidity control system - Yulu Chen; Akihito Ozaki; Haksung Lee; Zao Li (Building and Environment, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

A coral-derived neuropeptide suppresses pentylenetetrazol (PTZ)-induced epileptic seizures and improves recognition memory deficits by modulating NPY-Y1R - Qian Chen; Congshuang Deng; Xiaoshan Huang; Aili Wang; Nan Xu; Kaixun Cao; Min Yang; Shang Li; Qiumin Lu; Guiyi Gong; Simon Ming-Yuen Lee (Archives of Toxicology, 2026)
Epilepsy is a prevalent neurological disorder characterized by recurrent and unprovoked seizures. Despite the availability of anti-epileptic drugs (AEDs), a significant number of patients are still suffering from drug-resistant epilepsy. Neuropeptide Y (NPY) signaling system has emerged as a potential target for the development of anti-epileptic drugs due to its modulation of epileptic activity. In this study, we investigated the therapeutic potential of our previously discovered Scleractinia-derived NPY-like peptide (TpNPY) in seizure disorders. The anticonvulsant effects of TpNPY were evaluated using PTZ-induced seizures in zebrafish and mice in vivo. Furthermore, the underlying molecular mechanisms of TpNPY were assessed using glutamate-induced excitotoxicity models in HT22 mouse hippocampal cells in vitro. Our findings indicated that TpNPY could alleviate PTZ-induced seizure behavior, reduce the expression of seizure-associated immediate-early genes and the production of Reactive Oxygen Species (ROS) in zebrafish. In mice, TpNPY improved seizure behaviors, decreased inflammatory cytokine levels, and ameliorated abnormal glial activation in a PTZ kindling epileptic model. Besides, the administration of TpNPY could attenuate the PTZ-induced anxiety levels and improve recognition memory deficits. Moreover, TpNPY promotes neurogenesis and neural synaptic plasticity through the BDNF/TrkB signaling pathway. Additionally, TpNPY restored cell injury and attenuated oxidative stress in glutamate-challenged HT22 cells through the Nrf2/HO-1 signaling pathway. These results highlight the potential therapeutic efficacy of TpNPY in the treatment of seizures and provide new insights into the development of coral-derived anti-epileptic peptide-based drugs.

Determination of dissolved inorganic carbon export and the controlling factors in small mountainous Rivers, Taiwan - Man-Ching Choi; Pei-Hao Chen; Chi-Wang Tsui; Jr-Chuan Huang; Jun-Yi Lee; Li-Chin Lee (Journal of Hydrology, 2025)

Dual-functional C60-modified Ce-MOF for long-term free radical scavenging and facilitates tetracycline detection - Chih-Jou Kuo; Yi-Lun Chen; Ping-Chen Hsieh; Li Chen; Er-Chieh Cho; Kuen-Chan Lee (Journal of Environmental Chemical Engineering, 2025)

Palladium-catalyzed thermo, photo, and electrocatalytic CO₂ conversion to methanol and formaldehyde: A review of mechanistic pathways using synthetic, biogas, and fossil-derived CO2 - Yen-Yi Lee; Masimukku Srinivaas; I.-Cheng Li; Kapa Keharika; Rajender Boddula; Ramyakrishna Pothu; Sanna Gull; Bo-Wun Huang; Jein-Wen Chen; Prashanth W. Menezes; Guo-Ping Chang-Chien (Journal of Environmental Chemical Engineering, 2025)

Fabrication of dBSA@Hemin@Ag nanozyme based biosensor and application for the assessment of longitudinal concentration changes of choline in human breast milk - Peng Liu; Huimin Deng; Huijun Chen; Jiaoyang Li; Liangyi Hong; Huimin Zou; Xingyan Zhou; Hian Kee Lee; Zhenzhen Huang (Food Chemistry, 2025)

CuO/PVA-based ultra-low-volume oral H2S detection system to reveal tongue coating effects - Moumita Deb; Chang-Chuan Huang; Yen-Ming Lai; Chang-Ju Chu; Yu-Shan Lee; Chien-Ting Chen; William Lee; Hsin-Fei Meng; Li-Yin Chen; Olivier Soppera; Chao-Sung Lai; Ding-Han Wang; et al. (Chemical Engineering Journal, 2025)

Unveiling the role of Zn−N1S3 sites in atomic-precision ZnIn2S4/g-C3N4 heterostructure for highly efficient CO2-to-CO conversion - Hossam A.E. Omr; Raghunath Putikam; Mahmoud Kamal Hussien; Amr Sabbah; Tsai-Yu Lin; Kuei-Hsien Chen; Li-Chyong Chen; Heng-Liang Wu; Shien-Ping Feng; Ming-Chang Lin; Hyeonseok Lee (Chemical Engineering Journal, 2025)

D-band modulated bifunctional PdSn alloy nanozymes for advanced dual-mode biosensing - Jie Zhang; Zhaoying Wang; Changqing Li; Feng Tang; Shuangna Wang; Shuo Xing; Xiaofei Sun; Ning Chen; Zhongping Li; Shuai Zhang; Zonghoon Lee; Shujun Wang; et al. (Chemical Engineering Journal, 2025)

Editorial Expression of Concern: Expression of bioactive human interferon-gamma in transgenic rice cell suspension cultures - Tzy-Li Chen; Yi-Ling Lin; Yi-Ling Lee; Ning-Sun Yang; Ming-Tsair Chan (Transgenic Research, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Using HRMS fingerprinting to elaborate the effects of reclaimed water irrigation on small-molecule distribution in rice - Keng-Jui Lin; Wen-Ling Chen; Feng-Wen Chen; Yu-Chien Cho; Jin-Jing Lee; Shan-Li Wang (Journal of Environmental Management, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Planetary health diet and cognitive decline in Chinese older adults: Balancing health benefits and environmental sustainability - Zhaoyu Li; Kaisy Xinhong Ye; Mengxue Yang; Tih-Shih Lee; John Suckling; Lei Feng; Zhenglian Wang; Chen Chen (Food Research International, 2025)

Characterization of microbial communities in the rhizosphere and water of a field-scale artificial floating island system for nutrient removal - Zhaozhe Chen; Liangwei Li; Minseung Kim; Emma Lancaster; Jiyoung Lee; Ozeas S. Costa (Environmental Pollution, 2025)

Theaflavin 3,3′-digallate suppresses metastasis and reduces insulin-like growth factor-1-induced cancer stemness and invasiveness in human melanoma cells - Ju-Pi Li; Yi-Hsien Hsieh; Yi-Hsun Lee; Wen-Yi Tsai; Shun-Fa Yang; Yih-Shou Hsieh; Pei-Ni Chen (Chemico-Biological Interactions, 2025)

Mechanistic insights and clinical evidence of Helianthus annuus Linn. (Sunflower) seed oil for dermatological applications: A narrative review - Heng Chee Lim; Sue Kei Lee; Jing Wen Keng; Ee Qian Lee; Eugenie Sin Sing Tan; Kai Bin Liew; Chun Wai Mai; Siew Keah Lee; Li Chen; May Lee Low; Yik Ling Chew (Drug Delivery and Translational Research, 2025)

Streptococcus atopica sp. nov., Isolated from the Feces of a Toddler with Atopic Dermatitis - Chin-Kan Chan; Hui-Shan Wu; Li-Jyun Tsai; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yi-Sheng Chen (Current Microbiology, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Thiocyanate transformation mechanisms based on microbial metabolic and treatment technologies for thiocyanate-containing wastewater: A critical review - Yu-Tong Li; Yu Zhang; Wei Wang; Xue-Ting Wang; Xijun Xu; Aijie Wang; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Responses of anuran diversity and community structure to an urbanization gradient in a subtropical Asian city - Yung-Chih Lai; Cheng-En Li; Wei-Chun Cheng; Tien-Chen Lai; Pei-Fen Lee; Yi-Ju Yang (Urban Ecosystems, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Answer to comments on “Bamboo ecosystem services in 25 years: a systematic literature review of trends, insights, and knowledge gaps” - Chong-En Li; Shih-Yu Lee; Yi-Ying Chen; Shih-Yun Kuo; Mei-Hua Yuan (Environmental Science and Pollution Research, 2025)

Establishing coastal partnerships for sustainable development in Taiwan: A case of Shanshui area, Penghu - Wen-Hong Liu; Hsiao-Chien Lee; Shingo Akaike; Li-Shu Chen; Chih-Cheng Lin; Hu Chun-Chieh; Kuei-Chao Chang (Marine Policy, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Community shift of aquatic insects following waste-water treatment implementation at Dongda Creek, Taichung City, Taiwan - Lilibeth A. Bucol; Ching-Chen Lee; Lan-Wai Yeh; Li-Wei Wu; Jyh-Min Chiang (Journal of Asia-Pacific Entomology, 2025)

Optimization of oblique drone photogrammetry for avoiding sun glint in submerged seagrass mapping - Jundong Chen; Peiran Li; Jaeyong Lee; Xinlei Shao; Fan Zhao; Jun Sasaki (Estuarine, Coastal and Shelf Science, 2025)

Resolving the liquid repellency–mechanical durability trade-off via a biomimetic nacre-like superamphiphobic architecture - Tianhao Deng; Lishan Geng; Helong Zhang; Ruibo Ding; Xiong Qian; Lee Li; Tao Xu; Wenhua Wu; Zhi Chen; Junwu Chen; Yi Xie (Chemical Engineering Journal, 2025)

Metal plate reduction produces self-assembled graphene hydrogel for flexible all-carbon solid-state supercapacitors - Yen-Hsuan Li; Yu-Hsuan Ho; Jui-Chin Lee; I-Wen Peter Chen (Chemical Engineering Journal, 2025)

From AI to action: Antimicrobial peptides engineered by generative adversarial networks (GANs)-A novel approach to combat resistant Bacteria - Chia-Wen Lai; Chung-Yen Lin; Meng-Chen Tsai; Wei-Jung Chen; Chia-Chun Hsieh; Zi-Jing Lin; Li-Jiuan Shen; Ying-Lien Chen; Lee-Jene Lai; Shu-Hwa Chen; Yang-Hsin Shih (Chemical Engineering Journal, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Chemical and cell toxicity properties of particulate matter emitted from a diesel engine fueled with biodiesel and ethanol blends - Pak Kin Wong; Shou Hao Chen; Meisam Ahmadi Ghadikolaei; Kar Wei Ng; Simon Ming Yuen Lee; Jin Cheng Xu; Zhen Dong Lian; Lin Li; Shuli Li; Zhi Ning; Nirmal Kumar Gali; Adebayo Afolabi Fadairo (Environmental Pollution, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Interdecadal Variation of Spring Rainfall in Taiwan and Modulations of Global Warming and Pacific Decadal Oscillation - Wei‐Teh Li; Jau‐Ming Chen; I‐Huan Lee; Ruo‐Shan Tseng (International Journal of Climatology, 2025)
Spring rainfall in Taiwan during February–April (FMA) shows a profound decreasing trend in the period 1980–2022. This decreasing trend is found to be jointly modulated by the trend components of global warming and interdecadal evolutions of the Pacific Decadal Oscillation (PDO) from its positive to negative phase over the past four decades. In contrast, interdecadal oscillation components of the PDO weakly impact interdecadal decreases in Taiwan's spring rainfall. Both global warming and interdecadal PDO variability cause moderate warming in the tropical western North Pacific and strong warming over the northern North Pacific. The former causes height fields over the tropical western Pacific to shift northward to result in an anomalous cyclone in association with the weakening of the subtropical high to the south of Taiwan. This anomalous cyclone is also affected by a Matsuno‐Gill‐type response to sea surface temperature warming and an anomalous convergent centre over the tropical western Pacific around 150° E. In the northern North Pacific, strong SST warming displaces height fields northward to make an anomalous anticyclone via the weakening of the Aleutian Low. Taiwan is meridionally embedded by the above anomalous cyclone and anticyclone. This circulation pair induces anomalous easterly moisture flux to pass over Taiwan, which then turns southward into the South China Sea. Moisture transport from the tropical region toward Taiwan is suppressed, resulting in an evident decrease in spring rainfall.

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Bamboo ecosystem services in 25 years: a systematic literature review of trends, insights, and knowledge gaps - Chong-En Li; Shih-Yu Lee; Yi-Ying Chen; Shih-Yun Kuo; Mei-Hua Yuan (Environmental Science and Pollution Research, 2025)
While bamboo offers various benefits to people, existing reviews on the current state of knowledge and research trends regarding its ecosystem services remain limited. This study aims to systematically review the literature on bamboo ecosystem services, focusing on temporal and geographic patterns, thematic trends, and methodological approaches, as well as the exploration of synergies and trade-offs. It adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines and includes an analysis of 56 relevant studies indexed in Scopus. This review shows a recent growing academic interest in bamboo ecosystem services. Research is primarily concentrated in regions where bamboo is commonly found, shaped by regional research capacity, and characterized by both locally led efforts and externally conducted studies. Keyword and co-occurrence analyses identify three main research clusters focused on the quantitative assessment, qualitative investigation and economic valuation of ecosystem services. Methodologically, studies tend to rely on plot sampling for data collection, apply indices for analysis, and present findings through mapping and statistical techniques. Among ecosystem service categories, regulation and maintenance services receive the most attention. However, interactions among services remain underexplored, with research on synergies and trade-offs still limited. These findings provide valuable insights for bamboo forest management and indicate future research directions that merit deeper exploration.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

When crop straw meets CO2-intensive process industries in China: The potential of CO2 mitigation and techno-economic analysis - Minjiao Chen; Peng Jiang; Meihua Li; Guanhan Zhao; Han Lin; Liwen Mu; Lee Chung Lau; Jiahua Zhu (Biomass and Bioenergy, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

UV activated peroxymonosulfate synergistically removes Microcystis aeruginosa and Chlorella vulgaris - Huixin Li; Yu Luo; Min-Yong Lee; Hao Shen; Sisi Li; Hong Chen; Yanfei Zhou; Bingyu He; Bing Xie; Huan He; Xuejun Pan; Guohua Dao; et al. (Journal of Environmental Chemical Engineering, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Akkermansia muciniphila: promises and pitfallsfor next-generation beneficial microorganisms - Yantong Liu; Zonglun Li; Sze Ching Lee; Shurui Chen; Feifei Li (Archives of Microbiology, 2025)

Halogenated bisphenol F compounds: Chlorination-mediated formation and photochemical fate in sunlit surface water - Shengqi Zhang; Yuefei Ji; Kyriakos Manoli; Yong Li; Qian Chen; Yunho Lee; Xin Yu; Mingbao Feng (Water Research, 2025)

Tailored large-particle quantum dots with high color purity and excellent electroluminescent efficiency - Bo-Chen Liu; Qizhong Lin; Shuang-Qiao Sun; Qi Sun; Xing Peng; Xinyuan Chen; Yang Li; Yue-Min Xie; Shuit-Tong Lee; Man-Keung Fung (Science Bulletin, 2025)

Evaluation of heavy metal pollution and ecological risk of surface sediments in a tropical mountainous River-Estuary-Shelf Continuum system: A case study of the Selangor River, Malaysia - Aijun Wang; Chui Wei Bong; Shuqin Tao; Xiang Ye; Boyu Liu; Haoshen Liang; Xinqing Zheng; Yi You Wong; Kar Hoe Loh; Haiqi Li; Keliang Chen; Siew Huah Lim; et al. (Marine Environmental Research, 2025)

Unveiling the role of heteroatom doping and strain in Core-Shell catalysts for CO2RR - Yiran Bai; Yunjian Wang; Yibing Yang; Chen Sun; Hsiao-Tsu Wang; Chi-Feng Lee; Cheng-You Li; Tingting Zheng; Kunpeng Jiang; Lili Han (Chemical Engineering Journal, 2025)

Color variation and mate choice in a lacertid lizard - Wan-Xin Jian; Tsui-Wen Li; Fitra Arya Dwi Nugraha; Chen-Pan Liao; Tsung-Chen Lee; Ko-Huan Lee; Si-Min Lin (Behavioral Ecology and Sociobiology, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

Sample preparation using deep eutectic solvents in combination with nanomaterials in analytical procedures: A review - Ke Li; Jingyan Chen; Seulgi Kang; Jeongmi Lee (Analytica Chimica Acta, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

The Impact of Administrative Districts and Urban Landscape on the Dispersal of Aedes aegypti via Genetic Differentiation - Chin‐Gi Huang; Yi‐Cheng Tseng; Tsung‐Han Yu; Hui‐Ching Cheng; Tsung‐Ju Tsai; Jou‐Hsin Ting; Hsin‐Yi Ho; Ya‐Zhe Lee; Yen‐Chieh Chiu; Yu‐Ting Huang; Ting‐Chun Shih; Hsiang‐Yu Hsiao; et al. (Molecular Ecology, 2025)
Mosquito‐borne diseases affect millions and cause numerous deaths annually. Effective vector control, which hinges on understanding their dispersal, is vital for reducing infection rates. Given the variability in study results, likely due to environmental and human factors, gathering local dispersal data is critical for targeted disease control. To analyse the spread and differentiation of Aedes aegypti in southern Taiwan, we established a dengue vector monitoring network in Southern Taiwan's cities. This network employed GPS‐equipped ovitraps to gather eggs that were subsequently hatched in the laboratory and genotyped using genome‐wide SNP markers. From 168 individuals, we identified 757,238 SNPs for detailed analysis. The estimated effective dispersal distance was 154 m (95% CI: 126–180 m), consistent with prior mark‐release‐recapture (MRR) estimates. We discovered that geographic isolation significantly influences genetic differentiation at larger scales, such as between cities, whereas its correlation with genetic distances is considerably weaker at smaller scales, like within cities. This is likely due to the urban landscape in Taiwan, characterised by narrow roads and densely packed buildings, which facilitates extensive dispersal of Ae. aegypti. In evaluating potential barriers to Ae. aegypti dispersal, we found that roads had no significant impact, whereas administrative districts accounted for 4.8% of the population differentiation ( p −4 ). Surprisingly, this variation aligns with the effects of district‐specific mosquito control measures implemented at the municipal level. These findings highlight the complex interplay between urban landscapes, administrative measures and Ae. aegypti dispersal, emphasising the need for implementing targeted control strategies that consider these local dynamics.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Enhancing fish sludge bioconversion kinetics for nutrient recovery in aquaponics using a modified biological aerated filter with a novel media of polyhedral hollow spheres - Ang Chen; Hong Zhang; Yongxia Zi; Yueshu Gao; Chew Tin Lee; Chunjie Li (Journal of Environmental Management, 2025)

Synergistic effect of biochar and intercropping on lead phytoavailability in the rhizosphere of a vegetable-grass system - Muhammad Rizwan; Ghulam Murtaza; Zeeshan Ahmed; Qimei Lin; Xuejiao Chen; Imran Khan; Hamada Abdelrahman; Vasileios Antoniadis; Esmat F. Ali; Sang Soo Lee; Lijian Leng; Sabry M. Shaheen; et al. (Science of The Total Environment, 2024)

PM2.5 episodes in northern Taiwan under southerly winds in late winter - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Ja-Huai Lee; Wei-Che Lin; Meng-Hsuan Li; Shyh-Wei Chen; Shu-Hao Chang (Atmospheric Research, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

N-graphyne surrounded Bi2S3/BiOBr composites: In-situ ultrasound-assisted synthesis and superior photocatalytic activity - Xiangzhi Huang; Haohao Chen; Mingxuan Sun; Junjie Zhao; Huanying Teng; Yu Gao; Jun Li; S.W. Lee; J.G. Tang (Fuel, 2024)

Source characterization of the December 2018 Anak Krakatau volcano sector collapse - Xinghui Huang; Po Chen; En-Jui Lee; Xuejun Han; Li Sun; Qiang Xu (Natural Hazards, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Differential allelopathic effects of mangrove plants Kandelia obovata and Aegiceras corniculatum on harmful algal species: Potential applications in algal bloom control - Brian Yu-Keung Wong; Yang-Hang Chen; Kai-Hui Cui; Hai-Chao Zhou; Feng-Lan Li; Nora Fung-Yee Tam; Fred Wang-Fat Lee; Steven Jing-Liang Xu (Marine Pollution Bulletin, 2024)

Prediction of parameters in the Ibarra–Medina–Krawinkler model for reinforced concrete columns using random forest and active learning - Peng-Yu Chen; Kun-Chan Lee; Tsung-Lin Li (Soil Dynamics and Earthquake Engineering, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Ultrahigh humidity-resistance ppb-level formaldehyde sensing at room temperature induced by fluorinated dipole based "umbrella" and "bridge" - Sitao Lv; Liming Liu; Lanpeng Guo; Zhijian Mai; Honghao Chen; Chenxu Wang; Fengnan Wang; Hao Li; Yi-Kuen Lee; Ahmad M. Umar Siddiqui; Zichuan Yi; Guofu Zhou; et al. (Journal of Hazardous Materials, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

A solar-driven hygroscopic aerogel using electrical impedance tomography for exploiting differentiated photothermal interfaces - Miao Tang; Rongliang Yang; Jing Lin; Xupeng Lu; Connie Kong Wai Lee; Yang Xu; Siyu Chen; Haosong Zhong; Yexin Pan; Mitch Guijun Li (Chemical Engineering Journal, 2024)

Rapid tear screening of diabetic retinopathy by a detachable surface acoustic wave enabled immunosensor - Dhrubajyoti Das; Hsuan-An Chen; Chao-Li Weng; Yung-Chun Lee; Sheng-Min Hsu; Jae-Sung Kwon; Han-Sheng Chuang (Analytica Chimica Acta, 2024)

Use of consumer insights to inform behavior change interventions aimed at illegal pet turtle trade in China - Wuji Zheng; Anita Kar Yan Wan; Zhan Chen; Alexander Clark; Caitlin Court; Yuanlu Gu; Toby Park; Jake Reynolds; Xiaoxi Zhang; Lishu Li; Tien Ming Lee (Conservation Biology, 2024)
Illegal poaching and overexploitation for the international pet trade are among the greatest threats to freshwater turtles in Southeast Asia. Expanding consumer research in China is crucial to filling knowledge gaps about the scale and structure of illegal trade and developing audience‐targeted and relevant interventions that may reduce demand for illegal turtles as pets. We applied mixed methods to provide a detailed understanding of the consumer side of the illegal pet turtle trade in China. We conducted 30 interviews with key stakeholders and online surveys ( n = 2456) of turtle keepers via community forums. From these, we identified 3 core consumer groups based on their prior turtle‐keeping experience, species exposure, and potential for future purchases. We conducted a thematic qualitative analysis of concepts related to the capability, opportunity, motivation, and behavior (COM‐B) model to determine the factors influencing the illegal pet turtle trade and to identify barriers to illegal purchases. Specifically, we identified purchasers’ capabilities, opportunities, and motivations in the context of legality, enforcement risk, captive breeding, and impacts on wild population. We developed consumer journey maps (i.e., visual representations of customer's experiences throughout their buying journey) for core consumer groups. These maps illustrate the sequential behaviors and processes that consumers undertake when purchasing turtles, from initial exposure to sourcing, keeping, and providing a new home. Key factors influencing illegal purchases included convenient purchase channels, misguided cognition and motivations for pet keeping, and weak law enforcement. Effective interventions included messages focusing on shifting cognition and beliefs, increasing legal risk perception, and emphasizing stringent law enforcement, primarily delivered through online channels. Our results underscore the necessity for adaptable, audience‐tailored interventions to reduce consumer demand for illegal wildlife products. The mixed‐methods approach, combining quantitative and qualitative data, provided a comprehensive understanding of the target behavior and can inform the development of effective intervention strategies.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Development and Application of an Advanced Automatic Identification System (AIS)-Based Ship Trajectory Extraction Framework for Maritime Traffic Analysis - I-Lun Huang; Man-Chun Lee; Li Chang; Juan-Chen Huang (Journal of Marine Science and Engineering, 2024)
This study addresses the challenges of maritime traffic management in the western waters of Taiwan, a region characterized by substantial commercial shipping activity and ongoing environmental development. Using 2023 Automatic Identification System (AIS) data, this study develops a robust feature extraction framework involving data cleaning, anomaly trajectory point detection, trajectory compression, and advanced processing techniques. Dynamic Time Warping (DTW) and the Hierarchical Density-Based Spatial Clustering of Applications with Noise (HDBSCAN) algorithms are applied to cluster the trajectory data, revealing 16 distinct maritime traffic patterns, key navigation routes, and intersections. The findings provide fresh perspectives on analyzing maritime traffic, identifying high-risk areas, and informing safety and spatial planning. In practical applications, the results help navigators optimize route planning, improve resource allocation for maritime authorities, and inform the development of infrastructure and navigational aids. Furthermore, these outcomes are essential for detecting abnormal ship behavior, and they highlight the potential of route extraction in maritime surveillance.

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

Superwetting MAX@SiO2 coatings with high photothermal conversion performances for efficient seawater desalination and anti-/de-icing - Helong Zhang; Chuxiong Qiu; Rong Zhang; Hao Zhang; Yunxia Chen; Tao Zeng; Fen Qiao; Lee Li; Ghafar Ali; Xiujian Zhao; Yi Xie (Chemical Engineering Journal, 2024)

Streptococcus taoyuanensis sp. nov., a Novel Species Isolated from a Patient with Bacteremia - Chien-Yu Lee; Chin-Kan Chan; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Jia-rong Zhang; Hong-yu Chen; Li-Ting Wang (Current Microbiology, 2024)

Recycling and reuse of waste agricultural plastics with hydrothermal pretreatment and low-temperature pyrolysis method - Bingkun Chen; Feng Shen; Li Tong; Jiajiang Zhou; Richard Lee Smith; Haixin Guo (Chemosphere, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Green and efficient method to acquire high-value phycobiliprotein from microalgal biomass involving deep eutectic solvent-based ultrasound-assisted extraction - Ke Li; Chunxue Jiang; Sang-Il Han; Seulgi Kang; Jingyan Chen; Danbi Won; Yua Kang; Boyeon Bae; Yoon-E Choi; Hyung Sik Kim; Jeongmi Lee (Food Chemistry, 2024)

Facile fabrication of microfibrillated cellulose-based aerogels incorporated with nisin/β-cyclodextrin microcapsule for channel catfish preservation - Tao Gou; Wenxiu Li; Shenglin Chen; Chao Yi; Yu Guo; Zheng Cao; Lei Zhou; KangJu Lee; Mingrui Chen; Yaowen Liu (Food Chemistry, 2024)

CO2-induced switching between MOF-based bio-mimic slow anion channel and proton pump for medical exhalation detection - Honghao Chen; Xiaorui Yue; Yifei Fan; Bin Zheng; Sitao Lv; Fengnan Wang; Yixun Gao; Hao Li; Yi-Kuen Lee; Patrick J. French; Ahmad M. Umar Siddiqui; Yao Wang; et al. (Chemical Engineering Journal, 2024)

Amelioration of habitat since the early Holocene contributed to the origin of agriculture in the farming-pastoral zone of northern China - Xin Jia; Zhiping Zhang; Yonggang Sun; Runqi Jiang; Shuangwen Yi; Wei Chen; Jue Sun; Guoqiang Li; Shuzhi Wang; Enrui Li; Xiaonong Hu; Qingchun Bao; et al. (Science China Earth Sciences, 2024)

Effects of hypertension and use of antihypertensive drugs in pregnancy on the risks of childhood cancers in Taiwan - Helen T. Orimoloye; Ya-Hui Hu; Noah Federman; Beate Ritz; Onyebuchi A. Arah; Chung-Yi Li; Pei-Chen Lee; Julia E. Heck (Cancer Causes & Control, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Can conservation tillage and reduced irrigation promote sustainability in agroecosystems through lowering nitrous oxide emissions? A synthesis - Junjiang Chen; Guolin C. Li; Tien Ming Lee; Stavros D. Veresoglou (Plant and Soil, 2024)

An emerging pathogen found in farm-cultured fourfinger threadfin (Eleutheronema tetradactylum), Edwardsiella piscicida, its genetic profile, virulent genes, and pathogenicity - Li-Wu Cheng; Hsien-Chung Lee; Qiong-Yi Huang; Wen-Rou Huang; Pei-Chi Wang; Shih-Chu Chen (Aquaculture, 2024)

Hybrid plasmonic aerogel with tunable hierarchical pores for size-selective multiplexed detection of VOCs with ultrahigh sensitivity - Xin Liu; Tiehu Li; Yuhui Liu; Yiting Sun; Yanying Han; Tung Chun Lee; Amir Zada; Zeqi Yuan; Fei Ye; Jiahe Chen; Alei Dang (Journal of Hazardous Materials, 2024)

A multi-criteria simulation-optimization coupling approach for effective emergency response in marine oil spill accidents - Xudong Ye; Baiyu Zhang; Kenneth Lee; Rune Storesund; Xing Song; Qiao Kang; Pu Li; Bing Chen (Journal of Hazardous Materials, 2024)

Multi-functional ion-pairing additive for efficient quasi-2D perovskite light-emitting diodes and solar cells - Xiangrui Du; Ying Li; Zhongkai Yu; Chang‐Mok Oh; Yuanyuan Zhang; Fengwu Liu; Eunhye Yang; Yoomi Ahn; Yongzan Chen; In‐Wook Hwang; Bo Ram Lee; Fuqiang Li; et al. (Chemical Engineering Journal, 2024)

A bio-based, sweat-resistant and markedly sensitive iontronic skin for advancing central sleep apnea monitoring - Fenglong Li; Zhengyang Kong; Xiaolin Wang; Guyue Wang; Chao Chen; Ying Tian; Zhiyi Lyu; Kyung Jin Lee; Do Hwan Kim; Jung-Yong Lee; Jin Zhu; Wu Bin Ying (Chemical Engineering Journal, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Potential scale of industrial outputs of the bronze bell casting industry in 500 BCE China - Kin Sum Li; Haiwang Liu; Keith Wilson; Xueqing Chen; Kin San Lee; Qin Fang; Xu Qin; Yu Liu; Tsz Hin Chun; Haoran Jiang (Archaeological and Anthropological Sciences, 2024)
The potential scale of industrial outputs in the ancient world is often underestimated in current archaeological studies due to the lack of surviving artifacts for validation of the production scale. However, production traces left on extant artifacts can help us reconstruct production methods, and thus reveal the potential scale of production outputs of certain industries, even although there may not be a sufficient number of existing artifacts to demonstrate such volumes. The bronze bell casting industry operating in around 500 BCE in Xinzheng in Henan province, China, can be used as an example to demonstrate the then use by bell casters of the “pattern-block method” to efficiently create multiple bells sharing identical components. With their strong focus on efficiency, production speed, and low production costs, these casters intelligently designed assembly lines and assembled identical components replicated from models to prepare molds for casting. Knowledge of their production methods and currently preserved bells can provide evidence that the bell casting industry produced industrial outputs on a massive scale that was rare in the ancient world. This article also shows how innovative methods such as 3D model superimposition can be used to validate these hypotheses.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Functionalization of seawater reverse osmosis membrane with quorum sensing inhibitor to regulate microbial community and mitigate membrane biofouling - Chao Chen; Yu Yang; Chung-Hak Lee; Satoshi Takizawa; Zhenghua Zhang; How Yong Ng; Li-an Hou (Water Research, 2024)

The angiogenesis-modulating effects of coumarin-derivatives - Han-Ting Huang; Ching-Yuan Huang; Chih-Jou Lee; Bo-Jie Sun; Zong-Wei Jhang; Chi-Chung Wen; Yun-Hsin Wang; Tao-Sheng Li; Ching-Yuh Chern; Yau-Hung Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Efficient in situ saccharification of microcrystalline cellulose over immobilized cellulase on magnetic biochar in ionic liquid media - Junxi Lei; Limin Deng; Zongda Chen; Xiang Li; Kaixin Li; Jong-Min Lee (Chemical Engineering Journal, 2024)

Accelerating flow simulations in the built environment by using the fast fluid dynamics initializer - Chi Zhang; Chih-Yung Wen; Yu-Hsuan Juan; Yee-Ting Lee; Zhengwei Chen; An-Shik Yang; Zhengtong Li (Building and Environment, 2024)

Towards developing a matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI MSI) compatible tissue expansion protocol - Li-Cyun Chen; Chuping Lee; Cheng-Chih Hsu (Analytica Chimica Acta, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Biophysical mechanisms underlying tefluthrin-induced modulation of gating changes and resurgent current generation in the human Nav1.4 channel - Hsing-Jung Lai; Ming-Jen Lee; Hsin-Wei Yu; Kuan-Wen Chen; Ke-Li Tsai; Pi-Chen Lin; Chiung-Wei Huang (Pesticide Biochemistry and Physiology, 2024)

Surface hydrophobicity of boron nitride promotes PFOA photocatalytic degradation - Bo Wang; Yu Chen; Joshua Samba; Kimberly Heck; Xiaochuan Huang; Junseok Lee; Jordin Metz; Manav Bhati; John Fortner; Qilin Li; Paul Westerhoff; Pedro Alvarez; et al. (Chemical Engineering Journal, 2024)

Study on indoor thermal perception, behavioral adaptation in late pregnancy and their effects on adverse birth outcomes in south China - Jie Ni; Huailin Wang; Xinyue Yu; Run Gao; Yanqiu Li; Zhaosong Fang; Jason Kai Wei Lee; Zhenghong Zhu; Maimaitiminjiang Wulayin; Xin Chen; Cunrui Huang; Qiong Wang (Building and Environment, 2024)

Quantitative Proteomic and Phosphoproteomic Analyses Reveal a Role of Death-Associated Protein Kinase 1 in Regulating Hippocampal Synapse - Yuan Tian; Xiaoqing Zheng; Ruomeng Li; Li Hu; Xindong Shui; Long Wang; Dongmei Chen; Tae Ho Lee; Tao Zhang (Molecular Neurobiology, 2024)

Mussel-inspired modification of 2D MoS2 to construct a hybrid nanocomposite membrane with enhanced pervaporation dehydration of isopropanol - Marwin R. Gallardo; Jyun-Xiang Ciou; Chen-Hsiu Wang; Micah Belle Marie Yap Ang; Jeremiah C. Millare; Chi-Lan Li; Hui-An Tsai; Shu-Hsien Huang; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2024)

Critical Roles of Surface-Enhanced Heterogeneous Oxidation of SO2 in Haze Chemistry: Review of Extended Pathways for Complex Air Pollution - Zihao Zhang; Haiwei Li; Wingkei Ho; Long Cui; Qihui Men; Li Cao; Yunjiang Zhang; Junfeng Wang; Cheng Huang; Shun-cheng Lee; Yu Huang; Mindong Chen; et al. (Current Pollution Reports, 2024)

Exploring the association between campus environment of higher education and student health: A systematic review of findings and measures - Yizhen Ding; Chanam Lee; Xi Chen; Yang Song; Galen Newman; Ryunjung Lee; Sungmin Lee; Dongying Li; Wonmin Sohn (Urban Forestry & Urban Greening, 2024)

Adaptation behaviors modify the effects of body fat on heat-related symptoms among Taiwanese elderly - Chi-Hsien Chen; Wen-Yi Lin; Kang-Yun Lee; Wen-Jung Sun; Li-Ying Huang; Yue-Liang Leon Guo (International Journal of Hygiene and Environmental Health, 2024)

A flexible electrochromic device with variable infrared emissivity based on W18O49 nanowire cathode and MXene infrared transparent conducting electrode - Jing Zhao; Shengliang Zhang; Sheng Chang; Chong Li; Chang Fang; Xianjie Xia; Laifa Shen; Jim Yang Lee; Chen Cao; Xiaogang Zhang; Yimin Xuan (Chemical Engineering Journal, 2024)

Fabrication of chitin-glucan nanofibers: Insights into mushroom pretreatment and subsequent acidic deep eutectic solvent-based esterification - Danbi Won; Seulgi Kang; Ke Li; Boyeon Bae; Yua Kang; Jingyan Chen; Yu Seok Youn; Jeongmi Lee (Carbohydrate Polymers, 2024)

Genome‐wide characterization of microsatellites in cobia Rachycentron canadum (Linnaeus, 1766): Survey and analysis of their abundance and diversity - Mei‐Chen Tseng; Yen‐Hung Lee; Tsair‐Bor Yen; Shu‐Ming Li (Journal of Fish Biology, 2024)
The cobia Rachycentron canadum , mainly distributed in the warm waters of tropical and subtropical regions around the world, remains a fish of considerable economic importance. Detailed diversity and the number of microsatellite sequences in the cobia genome are still unintelligible. The primary aim of this work was to identify and quantify the miscellaneous SSR sequences in the cobia genome. More than 280,000 sequences were sequenced and screened using next‐generation sequencing technology and microsatellite identification. Perfect mononucleotide repeats, dinucleotide microsatellites, and trinucleotide microsatellites contain (A) 10 /(T) 10 , (AC) 6 /(TG) 6 , and (AAT) 5–32 as the largest number of motifs in each type of microsatellite, respectively. The tetranucleotide and pentanucleotide microsatellites (TTM and PTM) consist of the largest number of motifs of both (ATCT) 5–32 and (TCAT) 5–31 in TTMs, and (CTCTC) 5–9 in PTMs, whereas the hexanucleotide microsatellites are rarely observed in the cobia genome. All c . 38000 sequences of composite microsatellites are extremely diverse, including compound (11.71%), interrupted compound (71.77%), complex (0.45%), and interrupted complex (16.07%). In this study, we developed a convenient and useful recording system for writing down and categorizing diverse composite microsatellite types. This system will provide great support for exploring repeat origins, evolutionary mechanisms, and the application of polymorphic microsatellites.

Antagonizing pathological α-synuclein-mediated neurodegeneration by J24335 via the activation of immunoproteasome - Zhijian Pan; Chao-Wu Yu; Chen Zhao; Min Shao; Xuanjun Yang; Xiaonan Liang; Haitao Li; Yucong Lu; Qingqing Ye; Ji-Wang Chern; Jiahong Lu; Hefeng Zhou; et al. (Toxicology and Applied Pharmacology, 2023)

Characteristic and health risk of per- and polyfluoroalkyl substances from cosmetics via dermal exposure - Xia Lin; Yudong Xing; Huijun Chen; Yan Zhou; Xin Zhang; Peng Liu; Jiaoyang Li; Hian Kee Lee; Zhenzhen Huang (Environmental Pollution, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Environment-friendly organic coordination design of Z-scheme heterojunction N-BOB/BiOIO3 for efficient LED-light-driven photocatalytic and electrochemical performance - Yi-Lun Chen; Li Chen; Ming-Yen Sung; Jung-Hua Lin; Chao-Jan Liu; Chih-Jou Kuo; Er-Chieh Cho; Kuen-Chan Lee (Chemosphere, 2023)

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

First principal observation documenting the three-dimensional uptake of cadmium and spatial distribution of cadmium hydroxyapatite mineral in bone char - Partha Pratim Biswas; Jagat Rathod; Ching-Yu Chiang; Biqing Liang; Chun-Chieh Wang; Yao-Chang Lee; Yu-Chun Chuang; Prakash C. Loni; Wei-Hsin Chen; Shan-Li Wang (Chemosphere, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Strong variation of near-surface seismic anisotropy in Taiwan and its geological implications - Hsin-Yu Lee; Yuancheng Gung; Li-Wei Chen; Wen-Shan Chen; Ying-Nien Chen; Sheng-Jyun Cai; Hui-Chu Chen; Che-Wei Liao (Earth and Planetary Science Letters, 2023)

Association of Ferroptosis with Severity and Outcomes in Acute Ischemic Stroke Patients Undergoing Endovascular Thrombectomy: A Case-control Study - Shin-Joe Yeh; Chih-Hao Chen; Yen-Heng Lin; Li-Kai Tsai; Chung-Wei Lee; Sung-Chun Tang; Jiann-Shing Jeng (Molecular Neurobiology, 2023)

Spatial-temporal changes of compound temperature-humidity extremes in humid subtropical high-density cities: An observational study in Hong Kong from 1961 to 2020 - Yueyang He; Zixuan Wang; Hau Man Wong; Guangzhao Chen; Chao Ren; Ming Luo; Yuguo Li; Tsz-cheung Lee; Pak Wai Chan; Janice Ying-en Ho; Edward Ng (Urban Climate, 2023)

Trace Ru-tuned NiO/CNT electrocatalysts outperform benchmark Pt for alkaline hydrogen evolution with superior mass activity - Yanjun Chen; Yiyang Lee; Wei Chu; Jing Li (Chemical Engineering Journal, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Enhanced alginate-like exopolymers recovery from algal-bacterial aerobic granular sludge: Optimal cultivation condition and contribution of bacteria and microalgae during the transport/storage period - Xingyu Chen; Jinfei Mai; Xiaochuan Dong; Qian Wang; Zejiao Li; Tian Yuan; Zhongfang Lei; Zhenya Zhang; Kazuya Shimizu; Duu-Jong Lee (Bioresource Technology, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Quality of life and cost-effectiveness of different breast cancer surgery procedures: a Markov decision tree-based approach in the framework of Predictive, Preventive, and Personalized Medicine - Hon-Yi Shi; Chiu-Hui Li; Yen-Chen Chen; Chong-Chi Chiu; Hao-Hsien Lee; Ming-Feng Hou (EPMA Journal, 2023)

Highly efficient carbon assimilation and nitrogen/phosphorus removal facilitated by photosynthetic O2 from algal-bacterial aerobic granular sludge under controlled DO/pH operation - Zejiao Li; Jixiang Wang; Jialin Liu; Xingyu Chen; Zhongfang Lei; Tian Yuan; Kazuya Shimizu; Zhenya Zhang; Duu-Jong Lee; Yuemei Lin; Yasuhisa Adachi; Mark C.M. van Loosdrecht (Water Research, 2023)

A simulation technique for monitoring the real-time stress responses of various mooring configurations for offshore floating wind turbines - Mingsheng Chen; Chun Bao Li; Zhaolong Han; Jae-bin Lee (Ocean Engineering, 2023)

The effect of modifier adding sequence on physical-chemical property and adsorption ability of Inorganic-Organic Montmorillonite (IOMMt) - Jiajun Chen; Jianzun Lu; Sabrina Yanan Jiang; Chiu Hong Lee; Yu Li; Huada Daniel Ruan (Journal of Environmental Chemical Engineering, 2023)

Sulfur-induced electronic optimization of Mo5N6 for hydrogen evolution through topochemical substitution - Jianmei Chen; Xiaochun Liu; Hao Wang; Chao-Lung Chiang; Pengfei Hou; Jianmin Li; Huanyu Jin; Shujuan Liu; Xing Meng; Yan-Gu Lin; Jong-Min Lee; Qiang Zhao (Chemical Engineering Journal, 2023)

Enhancing the lithium-ion storage capability of Cu2ZnSnS4 anodes via a nitrogen-doped conductive support - Zeru Syum; Tadesse Billo; Amr Sabbah; Aswin kumar Anbalagan; Shaham Quadir; Adane Gebresilassie Hailemariam; Palani Sabhapathy; Chih-Hao Lee; Heng-Liang Wu; Li-Chyong Chen; Kuei-Hsien Chen (Chemical Engineering Journal, 2023)

Identification of Rhodosorus marinus isolated in Taiwan and study on its optimum culture conditions - Wei Qing Chloe Lung; Jane Wungen-Sani; Chi-Cheng Huang; Chien-Li Chen; Hung-Chih Lai; Yeh-Fang Hu; Po-Tsang Lee; Fan-Hua Nan; Han-Yang Yeh; Meng-Chou Lee (Journal of Applied Phycology, 2023)

Stochasticity dominates assembly processes of soil nematode metacommunities on three Asian mountains - Shuqi ZOU; Jonathan ADAMS; Zhi YU; Nan LI; Dorsaf KERFAHI; Binu TRIPATHI; Changbae LEE; Teng YANG; Itumeleng MOROENYANE; Xing CHEN; Jinsoo KIM; Hyun Jeong KWAK; et al. (Pedosphere, 2023)

Causal influences of salience/cerebellar networks on dorsal attention network subserved age-related cognitive slowing - Clive H. Y. Wong; Jiao Liu; Jing Tao; Li-dian Chen; Huan-ling Yuan; Mabel N. K. Wong; Yan-wen Xu; Tatia M. C. Lee; Chetwyn C. H. Chan (GeroScience, 2023)
Age-related cognitive slowing is a prominent precursor of cognitive decline. Functional neuroimaging studies found that cognitive processing speed is associated with activation and coupling among frontal, parietal and cerebellar brain networks. However, how the reciprocal influences of inter- and intra-network coupling mediate age-related decline in processing speed remains insufficiently studied. This study examined how inter- and intra-brain network influences mediate age-related slowing. We were interested in the fronto-insular salience network (SN), frontoparietal dorsal attention network (DAN), cerebellar network (CN) and default mode network (DMN). Reaction time (RT) and functional MRI data from 84 participants (aged 18–75) were collected while they were performing the Arrow Task in visual or audial forms. At the subject level, effective connectivities (ECs) were estimated with regression dynamic causal modelling. At the group level, structural equation models (SEMs) were used to model latent speed based on age and the EC mediators. Age was associated with decreased speed and increased inter-network effective connectivity. The CN exerting influence on the DAN (CN → DAN EC) mediated, while the SN → DAN EC suppressed age-related slowing. The DMN and intra-network ECs did not seem to play significant roles in slowing due to ageing. Inter-network connectivity from the CN and SN to the DAN contributes to age-related slowing. The seemingly antagonizing influences of the CN and SN indicate that increased task-related automaticity and decreased effortful control on top-down attention would promote greater speed in older individuals.

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Hierarchical ensembles of FeCo metal-organic frameworks reinforced nickel foam as an impedimetric sensor for detection of IL-1RA in human samples - Priya Vijayaraghavan; Yen-Yun Wang; Sathyadevi Palanisamy; Li-Yun Lee; Yuk-Kwan Chen; Shey-Cherng Tzou; Shyng-Shiou F. Yuan; Yun-Ming Wang (Chemical Engineering Journal, 2023)

Revealing calcium ion behavior during anaerobic phosphorus release process in aerobic granular sludge system - Jixiang Wang; Zejiao Li; Qian Wang; Xingyu Chen; Zhongfang Lei; Kazuya Shimizu; Zhenya Zhang; Yasuhisa Adachi; Duu-Jong Lee (Bioresource Technology, 2023)

Undescribed isoquinolines from Zanthoxylum nitidum and their antiproliferative effects against human cancer cell lines - Feng Qin; Cai Yi Wang; Chun-Gu Wang; Yao Chen; Jin-Jun Li; Mei-Shan Li; Yan-Kui Zhu; Sang Kook Lee; Heng-Shan Wang (Phytochemistry, 2023)

Facile fabrication of a 2D/2D CoFe-LDH/g-C3N4 nanocomposite with enhanced photocatalytic tetracycline degradation - Mengxue Li; Mengmeng Chen; Stephanie Ling Jie Lee; Sijie Lin (Environmental Science and Pollution Research, 2023)

Enhanced visible light-driven photodegradation of tetracycline by salicylic acid-modified graphitic carbon nitride and toxicity assessment - Mengmeng Chen; Mengxue Li; Peng Li; Stephanie Ling Jie Lee; Juanjuan Tang; Qian Li; Sijie Lin (Environmental Science and Pollution Research, 2022)

Oxygen vacancy engineering of photocatalytic nanomaterials for enrichment, activation, and efficient removal of nitrogen oxides with high selectivity: a review - Yanfeng Lu; Meijuan Chen; Liu Jiang; Jun-ji Cao; Haiwei Li; Shun Cheng Lee; Yu Huang (Environmental Chemistry Letters, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Assessment of brain connectome alterations in male chronic smokers using structural and generalized q-sampling MRI - Jun-Cheng Weng; Yu-Chen Chuang; Li-Bang Zheng; Ming-Shih Lee; Ming-Chou Ho (Brain Imaging and Behavior, 2022)

The impacts of ambient relative humidity and temperature on supine position-related obstructive sleep apnea in adults - Wen-Te Liu; Yuan-Hung Wang; Li-Te Chang; Chih-Da Wu; Dean Wu; Cheng-Yu Tsai; Chen-Chen Lo; Kang Lo; Kian Fan Chung; Ta-Yuan Chang; Kai-Jen Chuang; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Activation of multiple proteolysis systems contributes to acute cadmium cytotoxicity - Yen-Hsiu Yeh; Chia-Chih Tsai; Tien-Wen Chen; Chieh-Hua Lee; Wei-Jer Chang; Mei-Yi Hsieh; Tsai-Kun Li (Molecular and Cellular Biochemistry, 2022)

Shape stable poly(vinyl alcohol) hydrogels with immobilized metal hexacyanoferrates for cesium removal from waters - Po-Hsun Wang; Yin-Ru Chang; Man-Li Chen; Yu-Kuo Lo; Duu-Jong Lee (Environmental Science and Pollution Research, 2022)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Genomic characterization of a rare Carica papaya X chromosome mutant reveals a candidate monodehydroascorbate reductase 4 gene involved in all-hermaphrodite phenomenon - Jen-Ren Chen; Hiroki Ueno; Hideo Matsumura; Naoya Urasaki; Chen-Yu Lee; Fure-Chyi Chen; Shih-Wen Chin; Chun-Chi Liu; Chan-Tai Chiu; Kazuhiko Tarora; Jing-Yi Li; Chieh Ying Lee; et al. (Molecular Genetics and Genomics, 2021)

Identification of anti-HIV macrocyclic daphnane orthoesters from Wikstroemia ligustrina by LC–MS analysis and phytochemical investigation - Kouharu Otsuki; Mi Zhang; Takashi Kikuchi; Minami Tsuji; Miyuko Tejima; Zi-Song Bai; Di Zhou; Li Huang; Chin-Ho Chen; Kuo-Hsiung Lee; Ning Li; Kazuo Koike; et al. (Journal of Natural Medicines, 2021)

Pinocembrin-7-Methylether Protects SH-SY5Y Cells Against 6-Hydroxydopamine-Induced Neurotoxicity via Modulating Nrf2 Induction Through AKT and ERK Pathways - Zhi-Cong Zou; Ji-Jun Fu; Yuan-Ye Dang; Qian Zhang; Xiu-Fen Wang; Han-Bin Chen; Xue-Jing Jia; Simon Ming-Yuen Lee; Chu-Wen Li (Neurotoxicity Research, 2021)

Nucleophosmin/B23 promotes endometrial cancer cell escape from macrophage phagocytosis by increasing CD24 expression - Chiao-Yun Lin; Chia-Lung Tsai; Angel Chao; Li-Yu Lee; Wei-Chun Chen; Yun-Hsin Tang; An-Shine Chao; Chyong-Huey Lai (Journal of Molecular Medicine, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Molecular Imaging for Radiolabeling a PSMA-Targeted Long Circulating Peptide as a Theranostic Agent in Mice Bearing a Human Prostate Tumor - Ming-Hsin Li; Sheng-Nan Lo; Ming-Wei Chen; Wei-Lin Lo; Yuan-Ruei Huang; Shih-Ying Lee; Su-Jung Chen; Shih-Wei Lo; Shih-Ming Wang; Chih-Hsien Chang (Journal of Medical and Biological Engineering, 2021)

Middle Triassic (Anisian) Conodont Biostratigraphy at the Shaiwa Section, Guizhou, South China - Binxian Qin; Martyn Lee Golding; Haishui Jiang; Yan Chen; Muhui Zhang; Li Kang; Dacheng Wang; Jinling Yuan (Journal of Earth Science, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Design and synthesis of novel 7-[( N -substituted-thioureidopiperazinyl)-methyl]-camptothecin derivatives as potential cytotoxic agents - Zi-Long Song; Guan-Zhou Yang; Jun-Cai Li; Ying-Qian Liu; Chen-Jie Yang; Masuo Goto; Zhi-Jun Zhang; Susan L. Morris-Natschke; Hua Liu; Kuo-Hsiung Lee (Natural Product Research, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

The fertilization effect of global dimming on crop yields is not attributed to an improved light interception - Liping Shao; Gang Li; Qiannan Zhao; Yabing Li; Yutong Sun; Weinan Wang; Chuang Cai; Weiping Chen; Ronghua Liu; Weihong Luo; Xinyou Yin; Xuhui Lee (Global Change Biology, 2020)
Global dimming, a decadal decrease in incident global radiation, is often accompanied with an increase in the diffuse radiation fraction, and, therefore, the impact of global dimming on crop production is hard to predict. A popular approach to quantify this impact is the statistical analysis of historical climate and crop data, or use of dynamic crop simulation modelling approach. Here, we show that statistical analysis of historical data did not provide plausible values for the effect of diffuse radiation versus direct radiation on rice or wheat yield. In contrast, our field experimental study of 3 years demonstrated a fertilization effect of increased diffuse radiation fraction, which partly offset yield losses caused by decreased global radiation, in both crops. The fertilization effect was not attributed to any improved canopy light interception but mainly to the increased radiation use efficiency (RUE). The increased RUE was explained not only by the saturating shape of photosynthetic light response curves but also by plant acclimation to dimming that gradually increased leaf nitrogen concentration. Crop harvest index slightly decreased under dimming, thereby discounting the fertilization effect on crop yields. These results challenge existing modelling paradigms, which assume that the fertilization effect on crop yields is mainly attributed to an improved light interception. Further studies on the physiological mechanism of plant acclimation are required to better quantify the global dimming impact on agroecosystem productivity under future climate change.

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Correction to: In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

In Vitro Seeding Activity of Glycoform-Deficient Prions from Variably Protease-Sensitive Prionopathy and Familial CJD Associated with PrPV180I Mutation - Zerui Wang; Jue Yuan; Pingping Shen; Romany Abskharon; Yue Lang; Johnny Dang; Alise Adornato; Ling Xu; Jiafeng Chen; Jiachun Feng; Mohammed Moudjou; Tetsuyuki Kitamoto; et al. (Molecular Neurobiology, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Cloning, Expression and Characterization of Two Beta Carbonic Anhydrases from a Newly Isolated CO2 Fixer, Serratia marcescens Wy064 - Fanbing Chen; Wensong Jin; Huifang Gao; Zewang Guo; Hui Lin; Jiahuan Li; Kaihui Hu; Xiong Guan; Vipin C. Kalia; Jung-Kul Lee; Liaoyuan Zhang; Yongyu Li (Indian Journal of Microbiology, 2019)

High-resolution imaging of distinct human corpus callosum microstructure and topography of structural connectivity to cortices at high field - Byeong-Yeul Lee; Xiao-Hong Zhu; Xiufeng Li; Wei Chen (Brain Structure and Function, 2019)

Chronic low dose of AM404 ameliorates the cognitive impairment and pathological features in hyperglycemic 3xTg-AD mice - Hei-Jen Huang; Shu-Ling Chen; Hsin-Yu Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Hsiu Mei Hsieh-Li; Ming-Tsan Su (Psychopharmacology, 2019)

Benefit analysis of flood adaptation under climate change scenario - Hsin-Chi Li; Shih-Yun Kuo; Wei-Bo Chen; Lee-yaw Lin (Natural Hazards, 2019)

Effects of biochar-based fertilizers on nutrient leaching in a tobacco-planting soil - Yunlong Li; Jianzhong Cheng; Xinqing Lee; Yi Chen; Weichang Gao; Wenjie Pan; Yuan Tang (Acta Geochimica, 2019)

Physicochemical characterization and cytotoxicity of chitosan-modified single walled carbon nanotubes as drug carriers - Xiao-Xue Zhang; Hao-Yan Huang; Li-Qing Chen; Hehua Jin; Beom-Jin Lee; Jing-Hao Cui; Qing-Ri Cao (Journal of Pharmaceutical Investigation, 2019)

The combination of everolimus and terameprocol exerts synergistic antiproliferative effects in endometrial cancer: molecular role of insulin-like growth factor binding protein 2 - Angel Chao; Chiao-Yun Lin; Ren-Chin Wu; Yun-Shien Lee; Li-Yu Lee; Chia-Lung Tsai; Lan-Yan Yang; Hsuan Liu; Shu-Jen Chen; Tzu-Hao Wang; Chyong-Huey Lai (Journal of Molecular Medicine, 2018)

Factors regulating carbon sinks in mangrove ecosystems - Shi‐Bo Li; Po‐Hung Chen; Jih‐Sheng Huang; Mei‐Li Hsueh; Li‐Yung Hsieh; Chen‐Lu Lee; Hsing‐Juh Lin (Global Change Biology, 2018)
Mangroves are recognized as one of the richest carbon storage systems. However, the factors regulating carbon sinks in mangrove ecosystems are still unclear, particularly in the subtropical mangroves. The biomass, production, litterfall, detrital export and decomposition of the dominant mangrove vegetation in subtropical ( Kandelia obovata ) and tropical ( Avicennia marina ) Taiwan were quantified from October 2011 to July 2014 to construct the carbon budgets. Despite the different tree species, a principal component analysis revealed the site or environmental conditions had a greater influence than the tree species on the carbon processes. For both species, the net production (NP) rates ranged from 10.86 to 27.64 Mg C ha −1 year −1 and were higher than the global average rate due to the high tree density. While most of the litterfall remained on the ground, a high percentage (72%–91%) of the ground litter decomposed within 1 year and fluxed out of the mangroves. However, human activities might cause a carbon flux into the mangroves and a lower NP rate. The rates of the organic carbon export and soil heterotrophic respiration were greater than the global mean values and those at other locations. Only a small percentage (3%–12%) of the NP was stored in the sediment. The carbon burial rates were much lower than the global average rate due to their faster decomposition, indicating that decomposition played a critical role in determining the burial rate in the sediment. The summation of the organic and inorganic carbon fluxes and soil heterotrophic respiration well exceeded the amount of litter decomposition, indicating an additional source of organic carbon that was unaccounted for by decomposition in the sediment. Sediment‐stable isotope analyses further suggest that the trapping of organic matter from upstream rivers or adjacent waters contributed more to the mangrove carbon sinks than the actual production of the mangrove trees.

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Racial differences in the relationship between tobacco, alcohol, and the risk of head and neck cancer: pooled analysis of US studies in the INHANCE Consortium - Kristin J. Voltzke; Yuan-Chin Amy Lee; Zuo-Feng Zhang; Jose P. Zevallos; Guo-Pei Yu; Deborah M. Winn; Thomas L. Vaughan; Erich M. Sturgis; Elaine Smith; Stephen M. Schwartz; Stimson Schantz; Joshua Muscat; et al. (Cancer Causes & Control, 2018)

Selection of a Ligand-Binding Neutralizing Antibody Assay for Benralizumab: Comparison with an Antibody-Dependent Cell-Mediated Cytotoxicity (ADCC) Cell-Based Assay - Yuling Wu; Ahmad Akhgar; Jia J Li; Binbing Yu; Cecil Chen; Nancy Lee; Wendy I. White; Lorin K. Roskos (The AAPS Journal, 2018)

Establishment of two basal-like breast cancer cell lines with extremely low tumorigenicity from Taiwanese premenopausal women - Wen-Ling Kuo; Shir-Hwa Ueng; Chun-Hsing Wu; Li-Yu Lee; Yun-Shien Lee; Ming-Chin Yu; Shin-Cheh Chen; Chi-Chang Yu; Chi-Neu Tsai (Human Cell, 2018)

Effects of biochar on Cd and Pb mobility and microbial community composition in a calcareous soil planted with tobacco - Jianzhong Cheng; Yunlong Li; Weichang Gao; Yi Chen; Wenjie Pan; Xinqing Lee; Yuan Tang (Biology and Fertility of Soils, 2018)

Phase transition of iron sulphide minerals under hydrothermal conditions and magnetic investigations - Ssu Han Li; Yen-Hua Chen; Jey-Jau Lee; Hwo-Shuenn Sheu (Physics and Chemistry of Minerals, 2018)

Spectroscopic and molecular characterization of humic substances (HS) from soils and sediments in a watershed: comparative study of HS chemical fractions and the origins - Morgane Derrien; Yun Kyung Lee; Jae-Eun Park; Penghui Li; Meilian Chen; Sang Hee Lee; Soo Hyung Lee; Jun-Bae Lee; Jin Hur (Environmental Science and Pollution Research, 2017)

Cutaneous Exophiala oligosperma Infection in a Patient with Bullous Pemphigoid with a Review of the Literature - Chau Yee Ng; Sybren de Hoog; Hua-En Li; Yung-Yi Lee; Chun-Bing Chen; Pei-Lun Sun (Mycopathologia, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Lipid Nanoparticles Loaded with an Antisense Oligonucleotide Gapmer Against Bcl-2 for Treatment of Lung Cancer - Xinwei Cheng; Qibing Liu; Hong Li; Chen Kang; Yang Liu; Tianqi Guo; Ke Shang; Chengyun Yan; Guang Cheng; Robert J. Lee (Pharmaceutical Research, 2017)

Redistribution of Cav2.1 channels and calcium ions in nerve terminals following end-to-side neurorrhaphy: ionic imaging analysis by TOF–SIMS - Chiung-Hui Liu; Hung-Ming Chang; To-Jung Tseng; Chyn-Tair Lan; Li-You Chen; Su-Chung Youn; Jian-Jr Lee; Fu-Der Mai; Jui-Feng Chou; Wen-Chieh Liao (Histochemistry and Cell Biology, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

Development of Innovative Feedback Device for Swallowing Therapy - Chih-Ming Li; Hsiao-Yu Lee; Shang-Heng Hsieh; Tyng-Guey Wang; Hsueh-Pei Wang; Jia-Jin Jason Chen (Journal of Medical and Biological Engineering, 2016)

Adsorption of Pb(II) and Cu(II) metal ions on functionalized large-pore mesoporous silica - J.-Y. Lee; C.-H. Chen; S. Cheng; H.-Y. Li (International Journal of Environmental Science and Technology, 2016)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

Developmental and LED Light Source Modulation of Carotenogenic Gene Expression in Oncidium Gower Ramsey Flowers - Wen-Li Lee; Jian-Zhi Huang; Li-Chi Chen; Chi-Chu Tsai; Fure-Chyi Chen (Plant Molecular Biology Reporter, 2013)

A 2-yr service report of cell line authentication - Mei-Ling Wu; Li-Chuan Liao; Chiung-Yun Chen; Shin-Ying Lee; Gwo-Fang Yuan; Shiaw-Min Hwang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Increased precipitation during the Little Ice Age in northern Taiwan inferred from diatoms and geochemistry in a sediment core from a subalpine lake - Liang-Chi Wang; Hermann Behling; Teh-Quei Lee; Hong-Chun Li; Chih-An Huh; Liang-Jian Shiau; Su-Hwa Chen; Jiunn-Tzong Wu (Journal of Paleolimnology, 2013)

Antibacterial nanostructured composite films for biomedical applications: microstructural characteristics, biocompatibility, and antibacterial mechanisms - Fei-Peng Lee; Duen-Jeng Wang; Li-Kai Chen; Chun-Ming Kung; Yi-Chien Wu; Keng-Liang Ou; Chih-Hua Yu (Biofouling, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Baseline human papillomavirus infection, high vaginal parity, and their interaction on cervical cancer risks after a follow-up of more than 10 years - Shu-Fen Liao; Wen-Chung Lee; Hui-Chi Chen; Li-Chung Chuang; Mei-Hung Pan; Chien-Jen Chen (Cancer Causes & Control, 2012)

SARS-CoV nucleocapsid protein interacts with cellular pyruvate kinase protein and inhibits its activity - Wei-Yen Wei; Hui-Chun Li; Chiung-Yao Chen; Chee-Hing Yang; Shen-Kao Lee; Chia-Wen Wang; Hsin-Chieh Ma; Yue-Li Juang; Shih-Yen Lo (Archives of Virology, 2012)

A drug-laden elastomer for surgical treatment of anal fistula - Hairui Li; Bin Jiang; Jun Yan; Zhonghua Yang; Yanni Chen; Weiping Zhang; Alex C. Choy; Chi-Ying M. Lee; Lifeng Kang (Drug Delivery and Translational Research, 2011)

Isolation of a 2-oxetanone from the fruits of Synsepalum dulcificum - Ming-Jen Cheng; Wen-Li Lo; Lee-Yu Huang; Chyi-Jia Wang; Chung-Yi Chen (Natural Product Research, 2010)

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells - Yuan-Wei Shih; Shang-Tao Chien; Pin-Shern Chen; Jian-Hui Lee; Shu-Hau Wu; Li-Te Yin (Cell Biochemistry and Biophysics, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

5,5-Diphenyl-2-thiohydantoin-N10 (DPTH-N10) suppresses proliferation of cultured colon cancer cell line COLO-205 by inhibiting DNA synthesis and activating apoptosis - Tong-Sheng Lee; Li-Ching Chen; Yuan Liu; Jender Wu; Yu-Chih Liang; Wen-Sen Lee (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Geographic substructure of Fusarium asiaticum isolates collected from barley in China - Zheng Zhang; Hao Zhang; Theo van der Lee; Wan-Quan Chen; Paul Arens; Jin Xu; Jing-Sheng Xu; Li-Jun Yang; Da-Zhao Yu; Cees Waalwijk; Jie Feng (European Journal of Plant Pathology, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Registration of Micro-Computed Tomography and Histological Images of the Guinea Pig Cochlea to Construct an Ear Model Using an Iterative Closest Point Algorithm - Chia-Fone Lee; Gen-Jia Li; Shu-Yen Wan; Wen-Jeng Lee; Kai-Yuan Tzen; Chiung-Hsiang Chen; Yu-Lin Song; Yuan-Fang Chou; Yuh-Shyang Chen; Tien-Chen Liu (Annals of Biomedical Engineering, 2010)

Chemical constituents from the leaves of Michelia alba - Hui-Min Wang; Wen-Li Lo; Lee-Yu Huang; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Isolation of new aristolactam and dioxoaporphine from the leaves of Michelia compressa var. lanyuensis (Magnoliaceae) - Wen-Li Lo; Jin-Cherng Huang; Lee-Yu Huang; Chung-Yi Chen (Natural Product Research, 2010)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Streptomyces mayteni sp. nov., a novel actinomycete isolated from a Chinese medicinal plant - Hua-Hong Chen; Sheng Qin; Jae-Chan Lee; Chang-Jin Kim; Li-Hua Xu; Wen-Jun Li (Antonie van Leeuwenhoek, 2009)

A study of NO trafficking from dinitrosyl–iron complexes to the recombinant E. coli transcriptional factor SoxR - Feng-Chun Lo; Chang-Li Chen; Chien-Ming Lee; Ming-Che Tsai; Tsai-Te Lu; Wen-Feng Liaw; Steve S.-F. Yu (JBIC Journal of Biological Inorganic Chemistry, 2008)

Assessing the efficiency of a constructed wetland using a firstorder biokinetic model - Chih-Ju Jou; Shyh-Wei Chen; C. M. Kao; Chien-Li Lee (Wetlands, 2008)

Modeling Recombinant Immunotoxin Efficacies in Solid Tumors - Kevin C. Chen; Junho Kim; Xinmei Li; Byungkook Lee (Annals of Biomedical Engineering, 2008)

Bioequivalence Approaches for Highly Variable Drugs and Drug Products - Sam H. Haidar; Barbara Davit; Mei-Ling Chen; Dale Conner; LaiMing Lee; Qian H. Li; Robert Lionberger; Fairouz Makhlouf; Devvrat Patel; Donald J. Schuirmann; Lawrence X. Yu (Pharmaceutical Research, 2008)

Cardioprotection induced by hydrogen sulfide preconditioning involves activation of ERK and PI3K/Akt pathways - Yeshi Hu; Xin Chen; Ting-Ting Pan; Kay Li Neo; Shiau Wei Lee; Ester Sandar Win Khin; Philip K. Moore; Jin-Song Bian (Pflügers Archiv - European Journal of Physiology, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Diversity of culturable actinobacteria isolated from marine sponge Haliclona sp. - Shumei Jiang; Wei Sun; Minjie Chen; Shikun Dai; Long Zhang; Yonghong Liu; Kyung Jin Lee; Xiang Li (Antonie van Leeuwenhoek, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Use of herbicide-resistant genic male sterility in hybrid rice seed production - Sung Soo Kim; Jae Youn Jung; Seung Kwon Jeong; Dong Sun Lee; Li Juan Chen; Hak Soo Suh (Euphytica, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Opposing Action of Estrogen Receptors α and β on Tumor Necrosis Factor-α Gene Expression and Caspase-8-mediated Apoptotic Effects in HA22T Cells - Erh-Jung Huang; Cheng-Chung Wu; Shin-Da Lee; Juen-Hau Chen; Jer-Yuh Liu; Jiunn-Liang Ko; James A. Lin; Min-Chi Lu; Li-Mien Chen; Chih-Yang Huang; Wei-Wen Kuo (Molecular and Cellular Biochemistry, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Genetic characterization and fine mapping of a novel thermo-sensitive genic male-sterile gene tms6 in rice (Oryza sativa L.) - Dong Sun Lee; Li Juan Chen; Hak Soo Suh (Theoretical and Applied Genetics, 2005)

A Water Budget Model for the Yun-Lin Plain, Taiwan - Jin-Fa Chen; Cheng-Haw Lee; Tian-Chyi J. Yeh; Jin-Li Yu (Water Resources Management, 2005)

Recognition of Motor Imagery Electroencephalography Using Independent Component Analysis and Machine Classifiers - Chih-I Hung; Po-Lei Lee; Yu-Te Wu; Li-Fen Chen; Tzu-Chen Yeh; Jen-Chuen Hsieh (Annals of Biomedical Engineering, 2005)

Identification of a Lactose-Responsive Element Upstream of the Promoter of Bacillus megaterium β-Galactosidase-Encoding Gene mbgA - Jen-Ming Li; Chih-Yung Chiou; Tian-Ren Lee; Yuan-Shou Chen; Gwo-Chyuan Shaw (Current Microbiology, 2005)

Expression studies of mutations underlying Taiwanese Hunter syndrome (mucopolysaccharidosis type II) - Jui-Hung Chang; Shuan-Pei Lin; Shu-Chuan Lin; Kai-Li Tseng; Chia-Ling Li; Chih-Kuang Chuang; Guey-Jen Lee-Chen (Human Genetics, 2005)

Expression of bioactive human interferon-gamma in transgenic rice cell suspension cultures - Tzy-Li Chen; Yi-Ling Lin; Yi-Ling Lee; Ning-Sun Yang; Ming-Tsair Chan (Transgenic Research, 2004)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Repressed multidrug resistance genes in Streptomyces lividans - Li-Fong Lee; Yi-Jiun Huang; Carton W. Chen (Archives of Microbiology, 2003)

Control of recombinant human endostatin production in fed-batch cultures of Pichia pastoris using the methanol feeding rate - Zheng Jian Li; Qinghua Zhao; Hong Liang; Shunlin Jiang; Tom Chen; Davida Grella; Colleen Shearon; Donald P. Bottaro; B. Kim Lee Sim (Biotechnology Letters, 2002)

Dual action of palmitoyl trifluoromethyl ketone (PACOCF 3 ) on Ca 2+ signaling: activation of extracellular Ca 2+ influx and alteration of ATP- and bradykinin-induced Ca 2+ responses in Madin Darby canine kidney cells - Chung-Ren Jan; Kang-Ju Chou; Kam Chung Lee; Jue-Long Wang; Li-Ling Tseng; Jin-Shiung Cheng; Wei-Chuan Chen (Archives of Toxicology, 2000)

In vitro evaluation of GL331's cancer cell killing and apoptosis-inducing activity in combination with other chemotherapeutic agents - Tze-Sing Huang; Chih-Hung Shu; Chun-Chung Lee; Li-Tzong Chen; Jacqueline Whang-Peng (Apoptosis, 2000)

A Novel Podophyllotoxin-Derived Compound GL331 Is More Potent than Its Congener VP-16 in Killing Refractory Cancer Cells - Tze-Sing Huang; Chun-Chung Lee; Yee Chao; Chih-Hung Shu; Li-Tzong Chen; Li-Li Chen; Min-Hsiung Chen; Chiou-Chung Yuan; Jacqueline Whang-Peng (Pharmaceutical Research, 1999)